Empathy, Self-esteem, and Cyberbullying in vocational high school students - Wilantika, Rima; Khotimah, Husnul; Intansari, Fixi; Larasati, Bayu Sekar; Nabila, Julia; Saputri, Hindin; Mukhlis, Hamid (Utan Kayu Publishing, 2022)
Advances in technology have made internet access easier, this has changed the way humans communicate with one another in life. Along with the advancement and development of technology, teenagers are internet users who spend more time in the virtual world than the real world. However, the use of the internet is widely blamed for use by teenagers, one of the phenomena of internet abuse is cyberbullying. Cyberbullying is a form of harassment or humiliation through social media. Factors that influence cyberbullying are empathy and self-esteem. This study aims to determine the relationship between empathy and self-esteem with cyberbullying in vocational high school students. This research design uses quantitative, with the subject of Vocational High School students in Pringsewu as many as 90 students. The measurement tool for this study uses three scales, namely the empathy scale, the self-esteem scale, and the cyberbullying scale. The data analysis technique uses multiple regression analysis to determine the relationship between the independent variables and the dependent variable. The results of this study indicate that there is a significant relationship between empathy and self-esteem with cyberbullying in vocational high school students. That is, the higher the empathy and self-esteem, the cyberbullying behavior of low vocational high school students. On the other hand, the lower the level of empathy and self-esteem, the higher the level of cyberbullying among professional vocational high school students.